Impact of Proper Cargo-Handling on the Growth of the Douala Sea Port - Dr. Eyong Ako (Journal of World Economy, 2023)
This report entitled “THE IMPACT OF PROPER CARGO HANDLING ON THE GROWTH OF DOUALA SEAPORT” is set out to investigate cargo handling delays in Douala Seaport. Specifically, Douala Seaport and to proposed solutions to these difficulties. Data was collected using questionnaires, interview guide and observation and observation guide. Data was analysed using tables, frequency distribution data, percentage, valid percentage and cumulative percentages. To come up with the following findings that causes delay which include customs procedures, transport around the Unban area, loading and unloading of cargo at the port. The solutions as per these challenges are hastening customs procedures, reduction in customs procedures. The weight of cargo carried by trucks should be regulated in order to reduce traffic in and around the port. Also, reduction in customs procedures would enable proper cargo handling. The delay faced by most Douala Seaport is as a result of language barriers between customers and workers also less implementation of JIT by the firm. Also reducing the weight and number of trucks in and around the port at the same time will reduce traffic and also and also hastening the arrival of cargo at customer’s warehouse which fulfils the purpose of transportation as part of cargo handling.